Sikap dan tahap penguasaan ICT dalam kalangan guru-guru matematik di Sekolah Jenis Kebangsaan Tamil di Kedah - Govindamah, Kuppusamy (2009)
Using ICT in teaching mathematics is deemed appropriate within the needs of today's mathematics education. ICT can influence teachers' teaching approaches and also pupils' learning of mathematics. Nevertheless, the question is how competent are mathematic teachers with regards to using ICT and what are their attitude and level of ICT competence in using ICT in their mathematics lessons? This study was conducted to survey the attitude and level of ICT competence among Tamil primary school mathematics teachers. This study also surveyed the constraints these teachers are facing in using ICT in their lessons. A total of 60 respondents, comprising of mathematics teachers from six primary schools in Kedah, were involved in this study. The analysis using Pearson correlation coefficient indicates that there is a significant relationship between the level of ICT competence and attitude of mathematics teachers towards using ICT in mathematics lessons